A General Guideline on Formulating an AC Optimal Power Flow Model for Optimal Operation Grid-Connected AC Transmission Network - Vilaisarn, Youthanalack; Phrakonkham, Sengprasong; Inthala, Soumek (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
AC optimal power flow analysis (ACOPF) has been widely used for determining the optimal electrical network operation. Nonetheless, understanding the AC optimal power flow (ACOPF) analysis is not an easy task due to the requirement of mathematical knowledge and understanding the concept of ACOPF itself. According to these challenges, this article proposed the guideline that seeks to help the reader (e.g., students) deeply understand the concepts of ACOPF as well as be able to formulate ACOPF model. The proposed guideline includes the basic theory for ACOPF, formulation and solution. In this work, a nonlinear ACOPF problem for optimal losses reduction for a transmission system has been used as an example application. The ACOPF problem is solved using MATLAB (i.e., fmincon), while comparing the numerical result with those delivered by commercial tools DIGSILENT for evaluating the solution. Finally, the 5-bus balanced system with modification close to the practical EDL transmission network structure, is employed for the test system.